THE ROLL OF SOME PLANT GROWTH REGULATORS ON SHOOTS MULTIPLICATION OF STEVIA PLANTS IN VITRO - & Khierallah, Al-Obaidy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This research was conducted to study the effect of some plant growth regulators on in vitro shoots multiplication of stevia (Stevia rebaudiana Bertoni). The experiments included tests of various combinations of KIN with IBA or IAA in the shoot multiplication. Results indicated that KIN at 1.0 mg. L-1 plus 0.3 mg. L-1 of IBA produced the highest number of shoots (3.5 shoots) while KIN at 1.5 mg. L-1 plus IBA at 1.0 mg. L-1 produced the lowest shoot length (1.14 cm).  Hormone free medium produced the highest rate of the leaves number reached 28.56 leaves. KIN and IBA interaction increased fresh and dry weight significantly.   Treatment contained 2.0 mg -1 KIN plus 0.3 mg. L-1 IBA produced the highest fresh weight (1.739 g) while 0.5 mg. L-1 KIN and 0.3 mg. L-1 IBA produced the highest dry weight (0.822 g). As for the effect of interaction between the IAA and KIN it was significant in the number of shoots formed. Interaction between 1.0 mg. L-1 KIN with 0.1 mg. L-1IAA produced the highest number of shoots (3.8 shoots). Shoots length reached 8.10 cm in the media with 0.3 mg. L-1 IAA only. The highest fresh weight (1.267 g) was achieved with the interaction between 1.0 mg. L-1 KIN and 0.3 mg. L-1 IAA while 0.5 mg. L-1IAA without KIN produced the highest dry weight reached 0.138 g.  Shoots multiplication was improved by incorporation of the cytokinin TDZ in culture media. Shoots number, fresh and dry weights were increased significantly by adding 0.05 mg. L-1 of TDZ at present of 0.3 mg. L-1 of IBA giving 6.6 shoots, 0.974 g and 0.144 g respectively while shoots length decreased significantly as media without TDZ produced the highest shoots length reached 9.32 cm. The above results can adopt for the successful in vitro shoot multiplication of Stevia plants.